Chickenheads, agents, mommies, and jockeys: the social organization of transnational commercial sex - Chin, Ko-lin (Crime, law and social change, 2011)
In the sex trafficking literature, the term "trafficker" is often used to refer to all the various actors who are involved in the business of transnational sex work. It thus includes those who recruit women in the source countries; those who transport victims across international borders; and those who manage and exploit the women in the various commercial sex venues in the destination countries. In this paper, we will look at some of the people who fall into these categories of being "traffickers." Our goal is to better understand the many people who are facilitating transnational commercial sex. We will explore their background characteristics, the reasons for their involvement in sex trafficking, their roles and functions in the business, and the nature of their relationships with the women who sell sex. We will also discuss the issue of whether, and to what extent, organized crime groups are involved as traffickers in the transnational sex trade. Our discussion is drawn from face-to-face interviews with commercial sex workers, and with sex ring operators and a variety of government officials.